2019
DOI: 10.1264/jsme2.me18168
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Screening of Indigenous Plant Growth-promoting Rhizobacteria from Different Rice Cultivars in Afghanistan Soils

Abstract: To develop biofertilizers for rice in Afghanistan, 98 plant growth-promoting rhizobacteria were isolated from rice plants and their morphological and physiological characteristics, such as indole-3-acetic acid production, acetylene reduction, phosphate and potassium solubilization, and siderophore production, were evaluated. The genetic diversity of these bacteria was also analyzed based on 16S rRNA gene sequences. Of 98 bacteria, 89.7% produced IAA, 54.0% exhibited nitrogenase activity, and 40% showed phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 39 publications
7
40
2
1
Order By: Relevance
“…The implementation of various species of Psuedomonas as PGPB on rice plant is well reported [ 140 , 141 ]. For instance, PGPB activities of P. putida strain RRF3 have been demonstrated through transcriptomic analysis of rice plant roots [ 133 ].…”
Section: The Pgpb As Biocontrol Agentmentioning
confidence: 99%
“…The implementation of various species of Psuedomonas as PGPB on rice plant is well reported [ 140 , 141 ]. For instance, PGPB activities of P. putida strain RRF3 have been demonstrated through transcriptomic analysis of rice plant roots [ 133 ].…”
Section: The Pgpb As Biocontrol Agentmentioning
confidence: 99%
“…Tests for IAA production revealed that BSP9 produced 31.90 µg/mL of IAA. In the same way, P. putida strain AF137 isolated from rice cultivars in Afghanistan soils produced 92.30 μg mL −1 and its inoculation enhanced root and shoot dry weights of rice [ 39 ]. Similarly, a rhizobacterial strain of P. putida FA-56 was assessed for in vitro IAA production and its inoculation significantly increased the growth parameters of tomato plants [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…ACC deaminase activity was assayed according to a method described by Perone and Glick [34] with modification. Effects of strain M15 T on rice growth was evaluated under liquid culture condition formulated with conventional nutrient composition from the International Rice Research Institute according to Habibi et al [35] with modification. The high-quality disease-free rice seeds were surface-sterilized.…”
Section: Analysis Of Plant Growth-promoting Characteristicsmentioning
confidence: 99%
“…After growth in CAS medium, we observed an orange halo surrounded by the colony indicative of siderophore production. Siderophores are low molecular-weight iron chelators that directly promote plant growth by converting unavailable ferric oxides into absorbable forms for plants or indirectly by binding to the available forms of iron in soil and depriving pathogens in the vicinity of iron [35,48]. The strain M15 T as IAA and siderophore-producing bacteria, has the potential to be developed into bio-fertilizer to enhance plant growth and induce plant resistence to pathogens.…”
Section: Analysis Of Plant Growth-promoting Characteristicmentioning
confidence: 99%